“A more disgraceful case it has seldom fallen to our lot to comment upon”: Medical Malpractice in 19th-Century New Brunswick - Brown, R. Blake (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2018)
This article contributes to the scant Canadian historical literature on patients suing doctors for malpractice. It examines a lengthy New Brunswick case, Key v. Thomson in which a jury in Saint Andrews granted the largest damage award in a malpractice suit anywhere in British North America/Canada during the 19th century. This contextualized study provides insight into cultural forces affecting the law, shows how individuals navigated legal processes, demonstrates the complexity and nuances of some malpractice disputes, and sheds light on the attitude of the medical profession to efforts of patient-plaintiffs to use the law to keep doctors accountable.